The influences of Risk Management Committee and Audit Committee towards voluntary risk management disclosure - Maizatulakma Abdullah,; Zaleha Abdul Shukor,; Mohd Mohid Rahmat, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The main objective of this study is to examine the influences of committees that are being appointed to manage risk towards voluntary risk management disclosure (VRMD) among non-financial companies in Malaysia. Non-financial companies will usually appoint either Risk Management Committee (RMC) or Audit Committee (AC) to manage their risks. Based on resource dependence theory, this study contends that the committees provide risk management resources particularly in terms of risk management information that could influence the VRMD. All data of VRMD, RMC and AC were collected from companies’ annual reports by using content analysis method. The sample in this study consisted of 395 non-financial companies which were listed on Bursa Malaysia in 2011. Our multiple regression results show that RMC presence and AC activeness increase VRMD. Our findings provide evidence that the establishment of RMC could increase the risk management disclosure among companies in Malaysia.